Reduction of High School Ice Hockey Injuries With Implementation of New Checking/Boarding Rules. Issue 6 (November 2021) - Nadkarni, Lauren; Haskins, Amy; Holt, Christina; Dexter, William
Abstract : Objective: Evaluate whether rule changes by the National Federation of State High School Associations (NFHS) were associated with reduced injury rates in US high school ice hockey players. Design: We compared injury rates for the 3 seasons before the rule changes (2011-2012, 2012-2013, and 2013-2014) with the 2 subsequent seasons (2014-2015 and 2015-2016) using data from the High School Reporting Information Online (RIO) database. Setting: Convenience sample of US high schools. Participants: High school ice hockey athletes. Interventions: The sports injury surveillance system that supplied the data for this study was funded in part by the Centers for Disease Control and Prevention (grant Nos. R49/CE000674-01, R49/CE001172-01, and R49/CE002106-01) as well as research funding contributions of the NFHS, National Operating Committee on Standards for Athletic Equipment (NOCSAE), DonJoy Orthotics, and EyeBlack. The findings and conclusions in this report are those of the authors and do not necessarily represent the official position of the Centers for Disease Control and Prevention or any other funding agency. In the 2014 to 2015 ice hockey season, the NFHS increased the penalty for boarding (illegally causing opponent to be thrown violently into the boards) and for checking from behind. Main Outcome Measures: Injury rates and mechanism of injury. Results: There was a statistically significant 40% reduction in rates of injury attributed to being checked in the 2 seasons after the rule changes (5.0 injuries per 10 000 athlete exposures) compared with the 3 previous seasons (8.3) (rate ratio = 0.60, P = 0.002). There were no significant differences in overall injury rates ( P = 0.12) or injury rates due to checking ( P = 0.27), contact with the boards ( P = 0.31), or contact with another player ( P = 0.55). Conclusions: Among US high school ice hockey athletes, implementation of stricter penalties for boarding and checking from behind was associated with a significant decrease in injury rate due to being checked. Rates of injury due to other mechanisms were not significantly altered, suggesting the rule changes achieved their targeted effect. Abstract : Supplemental Digital Content is Available in the Text.